A Novel Top‐Down Synthesis of Ultrathin 2D Boron Nanosheets for Multimodal Imaging‐Guided Cancer Therapy. Issue 36 (18th July 2018) - Ji, Xiaoyuan; Kong, Na; Wang, Junqing; Li, Wenliang; Xiao, Yuling; Gan, Silvia Tian; Zhang, Ye; Li, Yujing; Song, Xiangrong; Xiong, Qingqing; Shi, Sanjun; Li, Zhongjun; et al.
Abstract: Single atom nonmetal 2D nanomaterials have shown considerable potential in cancer nanomedicines, owing to their intriguing properties and biocompatibility. Herein, ultrathin boron nanosheets (B NSs) are prepared through a novel top‐down approach by coupling thermal oxidation etching and liquid exfoliation technologies, with controlled nanoscale thickness. Based on the PEGylated B NSs, a new photonic drug delivery platform is developed, which exhibits multiple promising features for cancer therapy and imaging, including: i) efficient NIR‐light‐to‐heat conversion with a high photothermal conversion efficiency of 42.5%, ii) high drug‐loading capacity and triggered drug release by NIR light and moderate acidic pH, iii) strong accumulation at tumor sites, iv) multimodal imaging properties (photoacoustic, photothermal, and fluorescence imaging), and v) complete tumor ablation and excellent biocompatibility. As far as it is known, this is the first report on the top‐down fabrication of ultrathin 2D B NSs by the combined thermal oxidation etching and liquid exfoliation, as well as their application as a multimodal imaging‐guided drug delivery platform. The newly prepared B NSs are also expected to provide a robust and useful 2D nanoplatform for various biomedical applications. Abstract : Ultrathin 2D boron (B)‐based nanosheets (NSs) are fabricated through a novel top‐down approach by coupling liquid exfoliating and thermal oxidation etching, and applied to photonic drug delivery for cancer theranostics. The 2D B NS platform exhibits efficient photothermal conversion, high drug loading, spatiotemporally controlled drug release, strong tumor accumulation, good biocompatibility, and significant potential of multimodal imaging‐guided cancer treatment.